(untitled) (International Journal of Mathematics and Physics, 2021)
The control problem the first eigenvalues of the Euler-Bernoulli beam vibration with hinged and clamped fixings at both ends is considered. The control is based on Kanguzhin’s algorithm through integral perturbations of the boundary conditions of the original problem. Conditions for the boundary parameters for controlling the first eigenvalues are found.